2021
DOI: 10.3389/fpubh.2021.667251
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Survey on Professionals to Assess Health Needs of Newly Arrived Migrants in Spain

Abstract: Heightened conflicts and lack of safety due to reasons related to economic, social, ethnic, religious, sexual orientation, political, or nationality matters have increased migratory movements during the last, few decades. Unfortunately, when migrants arrive in new territories, they can face many barriers. For example, in Spain, some migrants have difficulties in accessing health services. The main objective of this study was to describe, from the perspective of social and healthcare professionals, health needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…It has been reported that socioeconomic or work conditions may elevate migrants’ exposure to health risks, which is worse for women, especially those in an irregular administrative standing. [ 1 ] Taking into consideration the main clinic departments the patients visited and the main health problems they suffered, demand for obstetrician-related services contributed to the high percentage of female patients. The 4 provinces in northern Vietnam that border Guangxi are economically underdeveloped.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that socioeconomic or work conditions may elevate migrants’ exposure to health risks, which is worse for women, especially those in an irregular administrative standing. [ 1 ] Taking into consideration the main clinic departments the patients visited and the main health problems they suffered, demand for obstetrician-related services contributed to the high percentage of female patients. The 4 provinces in northern Vietnam that border Guangxi are economically underdeveloped.…”
Section: Discussionmentioning
confidence: 99%
“…Migrants may face elevated health risks due to various new social determinants, such as socioeconomic or work conditions. [ 1 ] Health services are essential for their health maintenance. However, migrants’ access to health services may be compromised due to language barriers, cultural and religious differences, administrative issues, and discrimination from residents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear of deportation is also an obstacle for IMW seeking medical care; in countries like Sweden, clearer guidelines for healthcare professionals and IMW are needed [46]. Strategies for improving IMW's access to care include training professionals, giving IMW access to community volunteers and cultural mediators, and creating an open-door culture for accessing health care [47]. There is also a need to break down language barriers so that IMW can make medical appointments and avoid misunderstandings [10,18,24,35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Germany, Belgium, and Denmark provide access to emergency services while Spain provides guaranteed healthcare to all residents and due to reporting requirements in other countries, migrants are dissuaded from accessing health care altogether ( 20 – 22 ). Serre-Delcor et al ( 23 ) examine the health needs and barriers experienced by migrants resettled in Spain when they attempt to access health services. The authors conducted a perception-based cross-sectional survey among social and healthcare professionals who provide care to recently arrived migrants and noted three key findings.…”
Section: Differential Utilization Of Healthcare Servicesmentioning
confidence: 99%